Consumption of Fortified Wheat Flour and Associations with Anemia and Low Serum Ferritin in Colombia - Amy Fothergill; Zulma Y. Fonesca Centeno; Paul Rene Ocampo Téllez; Helena Pachón (Perspectivas en Nutrición Humana, 2019)
Background: Colombia’s mandatory wheat flour fortification program has yet to be evaluated. Objective: Examine associations between consumption of fortified wheat flour and low serum ferritin (LSF) and anemia prevalence. Materials and Methods: A secondary analysis of the 2005 national nutrition survey (ENSIN) was completed for 3988 children 2-4 y, 5669 children 5-12 y and 2053 non-pregnant women 13-49 y. The relationship between consumption (quartiles) of wheat flour containing food (WFCF) and LSF and anemia was examined using chi-square analyses and logistic regression models. Results: In adjusted models, controlling for socio-economic status, intake of animal-origin foods, and supplement use in the last 24 hours, a correlation was found between WFCF and anemia in the preschool aged group, when comparing the quartile of highest WFCF consumption with the lowest quartile (OR: 0.7, 95 % CI: 0.6-0.9). The prevalence of LSF was similar across all quartiles of WFCF consumption in all age groups. The highest prevalence of anemia was observed in the lowest WFCF consumption quartiles in all age groups, but was not significantly different in non-pregnant women 13-49 y. No association between WFCF and LSF was observed in adjusted or unadjusted models. Conclusions: In Colombia, consumption of wheat flour containing foods is associated with lower levels of anemia in pre-school aged children